Can't live without you - Hanlon, Abby (Dial Books for Young Readers, 2023)
Dory's separation anxiety from her mother turns into a ghostly, goofy escapade.
Ages 6-8 years.
Keywords: Separation anxiety -- Fiction; Mothers and daughters -- Fiction; Imagination -- Fiction; Family life -- Fiction; Humorous fiction; Novels